2008
DOI: 10.1038/ni.1637
|View full text |Cite
|
Sign up to set email alerts
|

A critical function for CD200 in lung immune homeostasis and the severity of influenza infection

Abstract: The lung must maintain a high threshold of immune 'ignorance' to innocuous antigens to avoid inflammatory disease that depends on the balance of positive inflammatory signals and repressor pathways. We demonstrate here that airway macrophages had higher expression of the negative regulator CD200 receptor (CD200R) than did their systemic counterparts. Lung macrophages were restrained by CD200 expressed on airway epithelium. Mice lacking CD200 had more macrophage activity and enhanced sensitivity to influenza in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
419
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(454 citation statements)
references
References 53 publications
22
419
4
Order By: Relevance
“…It is likely that these processes are regulated by CD200-CD200R through the same mechanism. Notably, infection of Cd200 À/À mice with Neisseria meningitides or influenza virus causes increased production of pro-inflammatory cytokines, including IL-1b, IL-6, tumor necrosis factora and interferong (Snelgrove et al, 2008;Mukhopadhyay et al, 2010). In our endogenous tumor model we also observed higher levels of the pro-inflammatory cytokines IL-1b and IL-6 in tumor-draining LN DCs derived from Cd200 À/À mice.…”
Section: Cd200-cd200r Signaling In Tumorigenesismentioning
confidence: 50%
“…It is likely that these processes are regulated by CD200-CD200R through the same mechanism. Notably, infection of Cd200 À/À mice with Neisseria meningitides or influenza virus causes increased production of pro-inflammatory cytokines, including IL-1b, IL-6, tumor necrosis factora and interferong (Snelgrove et al, 2008;Mukhopadhyay et al, 2010). In our endogenous tumor model we also observed higher levels of the pro-inflammatory cytokines IL-1b and IL-6 in tumor-draining LN DCs derived from Cd200 À/À mice.…”
Section: Cd200-cd200r Signaling In Tumorigenesismentioning
confidence: 50%
“…Steady-state intestinal Mjs express many inhibitory receptors including CD172a (SIRPa), CD200R1, IL-10R and receptors for TGF-b [10,38,39]. The ligands for each of these receptors are highly abundant in the intestine and in vitro studies have shown that some of these ligands can drive Mj differentiation into a pathway similar to that seen in the intestine.…”
Section: How Are Intestinal Macrophages Kept Inert?mentioning
confidence: 99%
“…The CD200/CD200 receptor (CD200R) axis has been reported to control myeloid cell activation [9,10] and to be crucially involved in the maintenance of lung immune homeostasis [11] in both human and mice [12,13]. The CD200 molecule is expressed on airways epithelial cells, endothelial cells and T cells [9,14], whereas the CD200R molecule is predominantly expressed on airway macrophages and neutrophils [13].…”
Section: Introductionmentioning
confidence: 99%
“…The CD200 molecule is expressed on airways epithelial cells, endothelial cells and T cells [9,14], whereas the CD200R molecule is predominantly expressed on airway macrophages and neutrophils [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation